Atomic-scale distorted lattice in chemically disordered equimolar complex alloys. (15th May 2018) - Ye, Y.F.; Zhang, Y.H.; He, Q.F.; Zhuang, Y.; Wang, S.; Shi, S.Q.; Hu, A.; Fan, J.; Yang, Y.
Abstract: It is a longstanding notion that alloying different sized elements can cause lattice distortion and phase transition in chemically complex alloys. However, a quantitative understanding of it remains difficult for traditional alloys, and becomes even more challenging for equimolar multicomponent alloys, also known as "high entropy alloys", which recently emerged as a promising structural/functional material and have been attracting tremendous research interest due to their unique properties. In this work, we carried out extensive first-principles calculations on a series of equimolar complex alloys with a chemically disordered crystalline structure, and characterized their atomic-scale lattice distortions in terms of the local residual strains. Albeit the confounding chemical/geometric complexities, we are able to show that the average attributes of such an atomic-scale distorted lattice, such as the lattice constant and the overall magnitude of the distortion induced residual strains, can be predicted very well by a simple physical model taking into account the efficient packing of different sized atoms interacting in an effective elastic medium. The findings of our current research unveils the details of locally distorted atomic packing in chemically disordered complex alloys, which sheds quantitative insights into the unusual strengthening mechanism as recently discovered in high entropy alloys. Graphical abstract: Image 1